IRON DEFICIENCY ANEMIA AFTER BYPASS SURGERY (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
All patients who have undergone BPSh and PRZh operations require daily oral iron supplementation at a minimum dose of 100 mg (in terms of elemental iron). In the case of development of ACD in a patient, in the absence of iron deficiency, taking iron supplements is inappropriate. Treatment in this case should be aimed at stopping the chronic inflammatory process in the remodeled small intestine.